Nanographene oxide-TiO2 photonic films as plasmon-free substrates for surface-enhanced Raman scattering - D. Papadakis; Diamantopoulou, A.; P.A. Pantazopoulos; D. Palles; E. Sakellis; N. Boukos; N. Stefanou; V. Likodimos (Nanoscale, 2019)
The development of nanostructured semiconductors with tailored morphology and electronic properties for surface-enhanced Raman scattering (SERS) has been attracting significant attention as a promising alternative to conventional coinage metal SERS substrates. In this work, functionalized TiO2 photonic crystals by graphene oxide nanocolloids (nanoGO) are demonstrated as highly sensitive, recyclable, plasmon-free SERS substrates that combine slow-photon amplification effects with the high adsorption capacity and surface reactivity of GO nanosheets. Comparative evaluation of photonic band gap engineered nanoGO-TiO2 inverse opal films was performed on methylene blue SERS detection under different laser excitations in combination with rigorous theoretical simulations of the photonic band structure. A very low detection limit of 6 × 10-7 M and an enhancement factor of 5 × 104 along with excellent self-cleaning performance and reusability could be achieved by the interplay of slow-photon effects assisted by interfacial charge transfer between the analyte and the nanoGO-TiO2 semiconducting substrate. Slow-photon management in combination with judicious engineering of chemical enhancement in photonic nanostructures is accordingly proposed as an advanced approach for the design of efficient dielectric SERS substrates. © 2019 The Royal Society of Chemistry.
cited By 4